Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia - Jacobsen, Ian P.; Bennett, Mike B. (Zootaxa, 2007)
A new atelomycterine catshark species (Scyliorhinidae: Atelomycterinae), Atelomycterus marnkalha n. sp., is described from north-east Australia (Great Barrier Reef Marine Park, Torres Strait and Gulf of Carpentaria). It differs from A. baliensis, A. marmoratus and A. macleayi in having posteroventally sloping dorsal fins, a lower precaudal vertebrae count and smaller adult size. Most similar to the Western Australian catshark species A. fasciatus, A. marnkalha differs from this species in having a larger anal fin, lateral denticles with prominent shallow depressions, claspers of adult males with a cover rhipidion lacking an obvious notch and its colour pattern with prominent white spots and fewer, smaller black spots.